Bank ownership and non-performing loans of Islamic and conventional banks in an emerging economy - Saw, Andrew Tek Wei; Ooi, Ai Yee; Yap, Woon Kan; Zurina Patrick; Syahrul Nizam Salam (Penerbit UPM, 2022)
This study assesses the non-performing loans of conventional and Islamic banks as well as the influence of ownership on the non-performing loans of conventional and Islamic banks. Due to fundamental differences in Islamic and conventional bank such as funding, non-performing loans might have differing effects on Islamic and conventional banks. This study utilised data of 26 conventional banks and 16 Islamic banks from Malaysia from 2012 to 2020. A Random Effect model was used to investigate the difference between conventional and Islamic banks’ non-performing loans as well as the influence of ownership on non-performing loans of conventional and Islamic banks. Results showed no significant differences for non-performing loans of conventional and Islamic banks. This result implies that despite the fact that Islamic banks may benefit from lower agency costs, this does not considerably decrease the likelihood of non-performing loans. Foreign Islamic banks shows higher non-performing loans in comparison to domestic Islamic banks. However, there were no significant differences for non-performing loans between foreign conventional and domestic conventional banks. This study suggests that Islamic bankers, particularly those intending to expand into other countries, investigate non-performing loans, which can impact the risk of a foreign Islamic bank.